Employee Performance Analysis of PT. Karya Indra Bagus Jaya - Amelia Oktavia Ardi Saputri; Sulastri Irbayuni (Indonesian Journal of Business Analytics, 2023)
The purpose of this study was to analyze the effect of workload, work discipline, and k3(occupational health and safety) on the performance of employees of PT. Karya Indra Bagus Jaya. This research method uses quantitative research where the dependent variable is employee performance and the independent variables in this study are workload, work disciplinel and and k3(keselamatan dan kesehatan kerja). The number of samples taken was 50 people. Sampling used saturated sampling method. The analysis technique uses the partial least squares (PLS) method. The results of this research analysis show that: 1) workload has an effect on the performance of employees of PT. Karya Indra Bagus Jaya, 2) work discipline has an effect on the performance of employees of PT. Karya Indra Bagus Jaya, 3) occupational safety and health affect the performance of employees of PT. Karya Indra Bagus Jaya.